Academic Challenges Faced by English-Major Freshmen in Their First Year - Jannah, Nisaul; Suharjito, Bambang; Andayani, Made Adi (Journal of Language, Communication, and Tourism, 2025)
In their first year of learning at the university, freshmen are usually put in transition.  Unlike other fields of study, freshmen majoring in English might encounter unique academic requirements, including language barriers, especially in a non-English-speaking country. This study aims to explore and describe the challenges in their first year and how they cope with them. Using semi-structured interviews, five freshmen were selected for data collection. The findings reveal some challenges English-major freshmen faced, including academic and language challenges, classroom experience and learning environment, and time management struggles. Due to these obstacles, participants employed various strategies to adapt, such as seeking peer support, adjusting study habits, and improving self-management. The study emphasized the importance of supporting first-year English-major students in their academic transition to achieve successful adaptation and integration. However, the use of a small number of samples and the particular institutional context in which the study was conducted limit the findings of the study.